Demographic Factors Affecting Customer's Perception toward the Use of Internet Banking in Pokhara Metropolitan City of Nepal - Ranabhat, Deepesh; Poudel, Hemkanta; Sapkota, Pradeep; Ranabhat, Mala (Journal of Business and Management, 2023)
Background: The provision of financial services to customers has been transformed by internet banking, which employs the internet as the primary means for carrying out banking transactions. Objectives: The research aims to assess the perception of customers toward the use of internet banking services and find out the demographic factors affecting it. Method: For this study, a descriptive and analytical research design was utilized, in which 225 customers of banks in Pokhara Metropolitan City of Nepal were purposively selected. The study employed various statistical techniques, including frequency distribution analysis, mean score analysis, and inferential analysis such as t-test and one-way ANOVA. Result: According to the study, most customers are aware of and have access of internet banking services. Customers of commercial banks view internet banking services to be simple, secure, and less expensive to use, with the bank providing adequate help. It was discovered that marital status, age, education, and economic level all affect awareness levels. Education influences access to internet and respondents' attitudes toward cost-saving are influenced by their marital status, education, and income level. Similarly, it was discovered that education, occupation, and income level aff ect the perception of ease of use, employment affects the impression of security, and marital status, education, and occupation affect the perception of bank assistance. Conclusions: The study concludes that marital status, educational qualification, monthly income of family, and working status are the major factors affecting the perception of the respondents toward the use of internet banking. Further, this study concludes that people of higher age and low education level are less aware of internet banking service.